Metastatic Prostate Cancer to the Left Temporal Bone: A Case Report and Review of the Literature - Erynne A. Faucett; Hal Richins; Rihan Khan; Abraham Jacob (Case Reports in Otolaryngology)
Breast, lung, and prostate cancers are the three most common malignancies to metastasize to the temporal bone. Still, metastatic prostate cancer of the temporal bone is a rare finding, with approximately 21 cases reported in the literature and only 2 cases discovered more than 10 years after initial treatment of the primary. This disease may be asymptomatic and discovered incidentally; however, hearing loss, otalgia, cranial nerve palsies, and visual changes can all be presenting symptoms. We present the case of a 95-year-old man with history of primary prostate cancer treated 12 years earlier that was seen for new-onset asymmetric hearing loss and otalgia. The tympanic membranes and middle ears were normal; however, based on radiologic findings and eventual biopsy, the patient was diagnosed with extensive metastatic prostate cancer to the left temporal bone. This case (1) demonstrates that a high index of suspicion for unusual etiologies of seemingly benign symptoms must be maintained in elderly patients having prior history of cancer and (2) substantiates the value of temporal bone imaging when diagnosis may be unclear from history and physical exam.